Globalized banks: Lending to emerging markets in the crisis - Nicola Cetorelli; Linda S. Goldberg (Federal Reserve Bank of New York, 2009)
As banking has become more globalized, so too have the consequences of shocks originating in home and host markets. Global banks can provide liquidity and risk-sharing opportunities to the host market in the event of adverse host-country shocks, but they can also have profound effects across international markets. Indeed, global banks played a significant role in the transmission of the current crisis to emerging-market economies. Flows between global banks and emerging markets include both cross-border lending, which has long been recognized as responding significantly to shocks at home or abroad, and internal capital-market lending, which is the internal flow of funds within a banking organization (such as between a headquarters and its offices in foreign locations). Adverse liquidity shocks to developed-country banking, such as those that occurred in the United States in 2007 and 2008, have reduced lending in local markets through contractions in cross-border lending to banks and private agents and also through contractions in parent banks' support of foreign affiliates. Because all these forms of transmission impinge on the lending channel in recipient markets, the ownership structure of emerging-market banks does not by itself provide sufficient basis for identifying the degree of shock transmission from abroad.
Keywords: E44; F36; G32; 330; Bank; global; liquidity; transmission; capital markets; cross-border lending